Tinjauan akad jual beli dan khiyar dalam situs bukalapak perspektif maslahah - Arina Dyah Puspita Sari; Ika Yunia Fauzia (Journal of Business & Banking, 2018)
Review Akad Buy Sell and Khiyar in a Site Bukalapak The Perspective Of Maslahah. This research reviewing the transactions by pelapak and buyers based on akad buy and sell khiyar associated with the maslahah in a site bukalapak. The collection of data by conducting interviews to informants as many as six people, three from the buyers, two of the pelapak, and one from the company at bukalapak. Data obtained processed and analyzed with the use of case studies, as well as tested their validity. Based on the results of the study, review of akad sell buy islamic perspective can use akad sell buy salam and akad murabahah. The akad used in accordance with the groove of sell buy on the site bukalapak, buyers see the goods and the price of goods and of order goods by paying in advance, recently received the goods within the period prescribed. The implementation of khiyar in the sharia perspective in site bukalapak use khiyar syarat and khiyar 'aib. Maslahah islamic perspective in site bukalapak which can be perceived by users i.e., bring benefits as well as resist damage. Researchers expect the results of this research can be beneficial to entrepreneurs islami and perpetrators of online business in indonesia.